Antibacterial fiber with high color stability and preparation method thereof
By adsorbing silver ions, antioxidants and anti-ultraviolet agents on kaolin and coating them with solid paraffin, the problem of discoloration of silver antibacterial agents under light and oxidation conditions is solved, and high color stability and antibacterial performance are improved.
Patent Information
- Application Number
- CN202310452822.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2022-04-26
- Filing Date
- 2023-04-25
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2043-04-25
AI Technical Summary
Silver antibacterial agents tend to discolor under light or oxidation conditions, affecting the appearance and antibacterial properties of the fibers.
Kaolin with reasonable particle size is used as a carrier to adsorb silver ions, antioxidants and anti-ultraviolet agents, and is coated by low-temperature drying and solid paraffin to form a stable composite structure to prevent the discoloration of silver antibacterial agents.
Effectively prevent silver antibacterial agents from discoloring under light and oxidation conditions, and improve the color stability and antibacterial properties of antibacterial fibers.
Smart Images

Figure CN116427044B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of antibacterial fiber processing, and in particular to an antibacterial fiber with high color stability and a preparation method thereof. Background Art
[0002] Microbial growth is a great hazard to public health, so antibacterial fibers have important social application value. Silver-based antimicrobial agents have excellent antibacterial properties, high bactericidal efficiency, and are not easy to develop drug resistance. They are widely used in the manufacture of antibacterial fibers. However, silver-based antimicrobial agents can change color and turn black under light or oxidation conditions, affecting the appearance of the fiber and may cause a decrease in antibacterial properties.
[0003] Patent application number CN200810123070.0 discloses a method for preparing a kaolin antibacterial agent carrying silver ions and copper ions. The method first prepares a solution of silver salt, sodium dihydrogen phosphate, copper salt, and water, and then mixes it with a kaolin raw material under stirring, and finally adds ammonium chloride and ammonium dihydrogen phosphate. After drying, crushing, calcining and re-crushing steps, the kaolin antibacterial agent carrying silver ions and copper ions is obtained. Although this method can solve the problem of silver ion discoloration to a certain extent, its essence is to cover the discoloration of silver that may occur by the blue color of copper sulfate, and the discoloration of silver is not fundamentally avoided. Therefore, it is of great significance to develop a new antibacterial fiber that can prevent the silver-based antibacterial agent from discoloring under light and oxidation conditions, and solve the stability problem of silver-based fibers.
[0004] In view of this, it is necessary to design an improved antibacterial fiber with high color stability and a preparation method thereof to solve the above problems. Summary of the invention
[0005] The object of the present invention is to provide an antibacterial fiber with high color stability and a preparation method thereof. First, kaolin with a reasonable particle size is selected to allow silver ions, antioxidants and anti-ultraviolet agents to be adsorbed on the surface and internal pores of the kaolin with a high specific surface area; then low-temperature drying is performed to remove moisture without destroying the molecular structure of the antioxidant and anti-ultraviolet agent; then solid paraffin is evenly wrapped on the surface of the composite kaolin, so that the stability of the composite structure adsorbed by kaolin is maintained to the greatest extent during the melt spinning process, thereby preparing a high-performance antibacterial fiber with high color stability.
[0006] To achieve the above-mentioned object of the invention, the present invention provides a method for preparing an antibacterial fiber with high color stability, comprising the following steps:
[0007] S1. Using calcined kaolin with a diameter of less than 500 nm as a carrier to adsorb silver ions, antioxidants and anti-ultraviolet agents to obtain composite kaolin; then drying the composite kaolin, coating the surface with solid paraffin to obtain a silver-based antibacterial composite; the silver ions, antioxidants, anti-ultraviolet agents and solid paraffin account for 30-40%, 5-10%, 3-5% and 5-10% of the total mass of the silver-based antibacterial composite, respectively;
[0008] S2. The silver-based antibacterial compound obtained in step S1 is mixed with a high molecular polymer in a preset ratio, and melt-spinned to obtain an antibacterial fiber with high color stability.
[0009] As a further improvement of the present invention, in step S1, the obtained composite kaolin is first dried at low temperature, and then solid paraffin is coated on the surface of the composite kaolin.
[0010] As a further improvement of the present invention, in step S1, solid paraffin is coated on the surface of the composite kaolin, specifically, the composite kaolin is preheated to 50-60°C, and then the preheated composite kaolin and the solid paraffin powder are quickly mixed so that the end surface of the solid paraffin in direct contact with the composite kaolin melts and adheres to the composite kaolin, thereby achieving the coating of kaolin by solid paraffin.
[0011] As a further improvement of the present invention, the temperature range of the low-temperature drying is room temperature-50°C; the low-temperature drying adopts one of low-temperature vacuum drying and low-temperature air flow drying.
[0012] As a further improvement of the present invention, in step S2, the temperature of the melt spinning does not exceed 260°C.
[0013] As a further improvement of the present invention, in step S2, the mass ratio of the silver-based antibacterial complex to the high molecular polymer is 3-9%:91-97%.
[0014] As a further improvement of the present invention, in step S1, kaolin is used as a carrier to adsorb silver ions, antioxidants and anti-ultraviolet agents. Specifically, the kaolin is first placed in a saturated concentration of silver nitrate solution and soaked for 30-50 minutes to adsorb silver ions; then the kaolin adsorbed with silver ions is placed in a saturated concentration of antioxidant and anti-ultraviolet mixed solution and soaked for 30-50 minutes to adsorb the antioxidant and anti-ultraviolet agent.
[0015] As a further improvement of the present invention, in step S1, the antioxidant is one of butylated hydroxyanisole, butylated hydroxytoluene, propyl gallate or tert-butylhydroquinone; and the anti-ultraviolet agent is one of benzophenone or benzotriazole compounds.
[0016] As a further improvement of the present invention, in step S3, the high molecular polymer is one of polyethylene, polypropylene, polyethylene terephthalate or polybutylene terephthalate.
[0017] To achieve the above-mentioned object of the invention, the present invention further provides an antibacterial fiber with high color stability, which is prepared by any of the above-mentioned methods for preparing antibacterial fibers with high color stability.
[0018] The beneficial effects of the present invention are:
[0019] (1) The method for preparing antibacterial fiber with high color stability provided by the present invention comprises the following steps: first, selecting kaolin with a reasonable particle size, allowing silver ions, antioxidants and anti-ultraviolet agents to be adsorbed on the surface and internal pores of the kaolin with a high specific surface area, thereby forming a composite structure adsorbed by kaolin; then, low-temperature drying is performed to remove moisture without destroying the molecular structure of the antioxidants and anti-ultraviolet agents, thereby maintaining the stability of the composite structure adsorbed by kaolin.
[0020] Then, the solid paraffin is evenly wrapped on the surface of the composite kaolin. As the temperature of the melt spinning process increases, the paraffin first isolates the high temperature from the damage of the antioxidant and the anti-ultraviolet agent to a certain extent; then it is heated and melted to absorb part of the heat. At the same time, the hollow structure of the kaolin can slow down the heat conduction rate inside it, improve the thermal stability of the load, and further reduce the heat absorbed by the antioxidant and anti-ultraviolet agent through the synergistic effect of the solid paraffin and kaolin, and avoid the high-temperature thermal decomposition of the organic matter of the antioxidant and anti-ultraviolet agent to the greatest extent, thereby maintaining the stability of the composite structure adsorbed by the kaolin to the greatest extent; at the same time, as the paraffin melts, the liquid paraffin is still wrapped on the surface of the composite kaolin. On the one hand, it is highly compatible with the antioxidant and anti-ultraviolet agent in the composite kaolin, and on the other hand, the paraffin is highly compatible with the high molecular polymer, so that the composite kaolin is evenly dispersed in the high molecular polymer, thereby preparing a high-performance antibacterial fiber with high color stability.
[0021] (2) The antibacterial fiber with high color stability provided by the present invention can prevent the silver-based antibacterial agent from changing color under light and oxidation conditions, thereby solving the problem of color stability of the silver-based antibacterial fiber and having a wide range of application scenarios. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 Figure 1 is a color fastness and durability graph of the antibacterial fiber with high color stability prepared in Example 1 and Comparative Example 16; Figure a is a color graph of the antibacterial fiber with high color stability prepared in Example 1 after storage for 3 months; Figure b is a color graph of the antibacterial fiber with high color stability prepared in Example 16 after storage for 3 months under the same conditions. DETAILED DESCRIPTION
[0023] In order to make the purpose, technical solutions and advantages of the present invention more clear, the present invention is described in detail below with reference to the accompanying drawings and specific embodiments.
[0024] It should also be noted that, in order to avoid obscuring the present invention due to unnecessary details, only structures and / or processing steps closely related to the scheme of the present invention are shown in the drawings, while other details that are not closely related to the present invention are omitted.
[0025] In addition, it should be noted that the terms "comprises", "includes" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or apparatus that includes a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or apparatus.
[0026] The present invention provides a method for preparing an antibacterial fiber with high color stability, comprising the following steps:
[0027] S1. Preparation of silver antibacterial complex:
[0028] The calcined kaolin with a diameter of less than 500 nm is used as a carrier to adsorb silver ions, antioxidants and anti-ultraviolet agents. Specifically, the kaolin is first immersed in a saturated silver nitrate solution for 30-50 minutes to adsorb silver ions; then the kaolin adsorbed with silver ions is immersed in a mixed solution of a saturated antioxidant and an anti-ultraviolet agent for 30-50 minutes to adsorb the antioxidant and the anti-ultraviolet agent to obtain a composite kaolin.
[0029] Next, the composite kaolin is dried at low temperature and then coated with solid paraffin on its surface. Specifically, the composite kaolin is preheated to 50-60°C, and then the preheated composite kaolin and solid paraffin powders are quickly mixed. Since the melting range of solid paraffin is 47-64°C, when the preheated kaolin and solid paraffin powders are quickly mixed, the end faces of the paraffin powders in direct contact with the composite kaolin are heated and fused and wrapped around the surface of the composite kaolin, forming a paraffin shell layer on the outer surface of the composite kaolin to obtain a silver-based antibacterial complex.
[0030] The silver ions, antioxidants, anti-ultraviolet agents and solid paraffin account for 30-40%, 5-10%, 3-5% and 5-10% of the total mass of the silver antibacterial complex respectively, and the rest is kaolin. The antioxidant is one of butylated hydroxyanisole, butylated hydroxytoluene, propyl gallate, tert-butylhydroquinone or other common antioxidants; the anti-ultraviolet agent is one of benzophenone, benzotriazole compound or other common antioxidants.
[0031] The temperature range of low-temperature drying of composite kaolin is room temperature-50°C (room temperature is usually 20°C); low-temperature drying adopts one of low-temperature vacuum drying and low-temperature air flow drying.
[0032] In this process, the particle size of the calcined kaolin is first controlled within 500nm. On the one hand, the kaolin with a high specific surface area can absorb a large amount of silver ions, antioxidants and anti-ultraviolet agents on its surface and internal pores by virtue of its hollow structure. At the same time, kaolin can firmly adsorb these substances, so that the silver ions are antibacterial and slowly released, achieving a long-lasting antibacterial effect. At the same time, the addition of antioxidants and anti-ultraviolet agents can prevent silver ions from changing color under the action of oxygen and light, further optimizing the antibacterial effect. On the other hand, the smaller particle size of kaolin fundamentally avoids the blockage of the subsequent melt spinning spinneret, providing favorable conditions for the subsequent melt spinning.
[0033] Then, the composite kaolin is dried by low-temperature drying. On the one hand, the drying process removes moisture on the surface and pores of the composite kaolin to avoid the influence of humidity on the melt spinning process (the melt spinning process is extremely sensitive to humidity, and when the humidity is higher than 5ppm, the melt spinning process of polyester cannot proceed normally); on the other hand, low-temperature drying is used to avoid the damage to the molecular structure of antioxidants and anti-self-exogenous agents caused by excessive temperature, thereby maintaining the structure of the composite kaolin to the greatest extent.
[0034] On this basis, the composite kaolin is wrapped by solid paraffin, and the solid paraffin is evenly adhered to the surface of the composite kaolin, thereby preventing moisture from entering the composite kaolin again during the storage process.
[0035] S2. Preparation of antibacterial fiber with high color stability:
[0036] The silver-based antibacterial compound obtained in step S1 is mixed with a high molecular polymer in a mass ratio of 3-9%:91-97%, and melt-spun at a temperature not exceeding 260° C. to obtain an antibacterial fiber with high color stability.
[0037] The high molecular polymer is one of polyethylene, polypropylene, polyethylene terephthalate (PET) or polybutylene terephthalate (PBT).
[0038] During the melt spinning process, firstly, the relatively high temperature will further evaporate the very small amount of water absorbed by the solid paraffin on the surface of the composite kaolin; secondly, the low heat transfer performance of the solid paraffin can to a certain extent isolate the damage of the antioxidant and anti-ultraviolet agent to the high temperature (antioxidants and anti-ultraviolet agents are usually not resistant to high temperatures); thirdly, as the temperature rises, the solid paraffin will absorb part of the heat during the melting process, further reducing the heat absorbed by the antioxidant and anti-ultraviolet agent, and avoiding the high-temperature thermal decomposition of the organic matter of the antioxidant and anti-ultraviolet agent to the greatest extent; in addition, solid paraffin is an organic matter, and as the paraffin melts, the liquid paraffin is still wrapped on the surface of the composite kaolin and is highly compatible with the antioxidant and anti-ultraviolet agent in the composite kaolin. At the same time, paraffin is highly compatible with high molecular polymers, so that the composite kaolin is evenly dispersed in the high molecular polymer, thereby preparing high-performance antibacterial fibers with high color stability.
[0039] The present invention also provides an antibacterial fiber with high color stability, which is prepared by the above-mentioned method for preparing the antibacterial fiber with high color stability.
[0040] The present invention is described in detail below through multiple embodiments.
[0041] Example 1
[0042] A method for preparing an antibacterial fiber with high color stability comprises the following steps:
[0043] S1. Preparation of silver antibacterial complex:
[0044] The calcined kaolin with a diameter of 300 nm is used as a carrier to adsorb silver ions, butylated hydroxyanisole and benzophenone to obtain a composite kaolin; then the composite kaolin is dried at 30°C, preheated to 60°C, and then the preheated composite kaolin and solid paraffin powder are quickly mixed to form a paraffin shell layer on the outer surface of the composite kaolin to obtain a silver-based antibacterial complex.
[0045] Among them, silver ions, butylated hydroxyanisole, benzophenone and solid paraffin account for 35%, 7%, 4% and 7% of the total mass of the silver-based antibacterial complex, respectively.
[0046] S2. Preparation of antibacterial fiber with high color stability:
[0047] The silver-based antibacterial composite obtained in step S1 is mixed with PET in a mass ratio of 7%:93%, and melt-spun at a temperature of 250° C. to obtain an antibacterial fiber with high color stability.
[0048] Examples 2-3 and Comparative Example 1
[0049] A method for preparing an antibacterial fiber with high color stability is provided. Compared with Example 1, the difference lies in that in step S1, the particle size of the calcined kaolin is different. The other details are substantially the same as Example 1 and will not be described in detail herein.
[0050] The antibacterial fibers with high color stability prepared in Examples 1-3 and Comparative Example 1 were tested for spinnability, and the results are shown in Table 1:
[0051] Table 1 Spinnable properties of antibacterial fibers prepared in Examples 1-3 and Comparative Example 1
[0052]
[0053] It can be seen from Table 1 that when the particle size of kaolin exceeds 500 nm (Comparative Example 1), the spinning process of melt spinning is seriously affected and spinning is basically impossible to achieve. This is mainly because when the particle size exceeds 500 nm, kaolin easily blocks the spinneret hole, resulting in the inability to spin normally.
[0054] If the particle size of kaolin is too small (less than 100nm), it is easy to agglomerate, thus affecting the solid paraffin coating. At the same time, it also has the disadvantage of not being able to be evenly distributed during the melt spinning process, which in turn affects the performance of the antibacterial fiber.
[0055] Examples 4-5 and Comparative Examples 2-3
[0056] A method for preparing an antibacterial fiber with high color stability is provided. Compared with Example 1, the difference is that in step S1, the proportion of solid paraffin to the total mass of the silver-based antibacterial composite is different, and the rest is substantially the same as Example 1 and will not be repeated here.
[0057] The performance of the antibacterial fibers with high color stability prepared in Examples 4-5 and Comparative Examples 2-3 was tested, and the results are shown in Table 2:
[0058] The antibacterial rate test refers to GB / T 20944.3-2008 "Oscillating method for evaluation of antibacterial properties of textiles", and the test data is the antibacterial rate data for Escherichia coli. The basic principle of the oscillation method test is: the test sample and the control sample are respectively placed in a conical flask with a certain concentration of test bacterial solution, oscillated at a specified temperature for a certain period of time, and the concentration of live bacteria in the bacterial solution in the conical flask before and after oscillation for a certain period of time is measured, and the inhibition rate is calculated to evaluate the antibacterial effect.
[0059] The initial antibacterial rate is to test the antibacterial rate of the newly prepared antibacterial fiber.
[0060] The light antibacterial rate is the antibacterial rate measured after the newly prepared antibacterial fiber is exposed to 300-400 nm light for 30 minutes. The changes in the initial antibacterial rate and the light antibacterial rate can explain the antibacterial and UV resistance of the antibacterial fiber.
[0061] The oxidative antibacterial rate is the antibacterial rate measured after the newly prepared antibacterial fiber is placed in the air (away from light or in a place without direct sunlight, etc.) for 3 months. The changes in the initial antibacterial rate and the oxidative antibacterial rate can explain the antibacterial and antioxidant properties of the antibacterial fiber.
[0062] In order to facilitate the observation of fiber color changes, the fibers prepared in this application are all white, and the whiteness grade of the fibers is detected using FZ / T01068-2009 "White Sample Card for Evaluating the Whiteness of Textiles". The whiteness grade of the fibers is divided into 5 levels, with 5 being the highest and 1 being the lowest. White antibacterial textiles containing silver ions will change from white to grayish black under ultraviolet light or long-term natural oxidation conditions. In the present invention, the anti-ultraviolet and anti-oxidation color stability of the fibers is evaluated by the change in whiteness grade. (After oxidation or ultraviolet light, when the whiteness remains at level four or drops from level four to level three, there is basically no obvious change in color, indicating that the whiteness is basically stable, and the fiber has good ultraviolet and antioxidant properties at this time; when the whiteness grade drops from level four to level two or level one, the fiber will undergo obvious changes, indicating that the fiber has poor ultraviolet and antioxidant properties at this time.)
[0063] The initial whiteness grade is to test the whiteness of the newly prepared antibacterial fiber.
[0064] The oxidation whiteness grade is the whiteness grade measured after the newly prepared antibacterial fiber is placed in the air (away from light or in a place without direct sunlight, etc.) for 3 months. The changes in the initial whiteness grade and the oxidation whiteness grade can explain the oxidation color fastness of the antibacterial fiber.
[0065] The specific test of light whiteness grade is as follows: refer to the irradiation method of GB / T 8427-2019 "Textiles - Color fastness to artificial light: Xenon arc" to treat the fiber with light; then use FZ / T 01068-2009 "White sample card for assessing the whiteness of textiles" to test the fiber whiteness grade before and after light exposure. The change of the initial whiteness grade and the light whiteness grade can explain the color fastness of the antibacterial fiber to light.
[0066] Table 2 Related properties of antibacterial fibers prepared in Examples 4-5 and Comparative Examples 2-3
[0067]
[0068] As shown in Table 2, when the content of silver ions, antioxidants and anti-ultraviolet agents remains unchanged, with the increase of solid paraffin content (Examples 1, 4, and 5), the initial antibacterial rate of the obtained antibacterial fiber continues to increase, even up to 100%. This is mainly because with the increase of solid paraffin content, the paraffin layer wrapped on the surface of the composite kaolin is more uniform and compact, and the composite kaolin is more evenly dispersed during the melt spinning process. At the same time, the solid paraffin has better protection against anti-ultraviolet agents and antioxidants, and the antibacterial properties of the obtained antibacterial fiber are better. At the same time, from the data of oxidation antibacterial rate and light antibacterial rate, oxidation whiteness grade and light whiteness grade, it can be seen that the obtained antibacterial fiber has good oxidation resistance and UV resistance.
[0069] When the solid paraffin content is too high (Comparative Example 3), although the paraffin layer wrapped on the surface of the composite kaolin is denser, during the melt spinning process, excessive paraffin content will reduce the viscosity of the melt after liquefaction, resulting in the inability to form fibers, seriously affecting the spinning process.
[0070] When the amount of solid paraffin added is too low (Comparative Example 2), the paraffin has poor encapsulation of kaolin, which makes the kaolin not only easy to agglomerate, but also the paraffin layer has weak protective effect on antioxidants and anti-ultraviolet agents. The antioxidants and anti-ultraviolet agents decompose at high temperatures, thereby affecting the antibacterial and light fastness of the resulting fiber. At the same time, the dispersion uniformity of kaolin in polyester is poor; in addition, with the continuous decomposition of antioxidants and anti-ultraviolet agents, the content of organic molecules in the pores of kaolin decreases, so the interaction between kaolin and paraffin is relatively weakened, which further affects the dispersion uniformity of kaolin in polyester and affects the antibacterial and color fastness of the resulting fiber.
[0071] Examples 6-7 and Comparative Examples 4-5
[0072] A method for preparing an antibacterial fiber with high color stability is provided. Compared with Example 1, the difference is that in step S1, the proportion of silver ions in the total mass of the silver-based antibacterial composite is different, and the rest is substantially the same as Example 1 and will not be repeated here.
[0073] The performance of the antibacterial fibers with high color stability prepared in Examples 6-7 and Comparative Examples 4-5 was tested, and the results are shown in Table 3:
[0074] Table 3 Related properties of antibacterial fibers prepared in Examples 6-7 and Comparative Examples 4-5
[0075]
[0076] It can be seen from Table 3 that when the content of antioxidants, anti-ultraviolet agents and solid paraffin remains unchanged, as the silver ion content continues to increase, the initial antibacterial rate continues to increase; when the silver ion content reaches a certain value, the antibacterial property of the fiber tends to be stable (Comparative Example 5).
[0077] However, when the silver ion content is high (Comparative Example 5), although the initial antibacterial rate is high, the silver ion content is too high at this time, and its content does not match the content of antioxidants and anti-ultraviolet agents, resulting in the antioxidants and anti-ultraviolet agents being unable to provide good protection for silver ions. Therefore, its oxidation whiteness level and light whiteness level are significantly reduced.
[0078] Examples 8-9 and Comparative Examples 6-7
[0079] A method for preparing an antibacterial fiber with high color stability, compared with Example 1, is different in that in step S1, the proportion of butylated hydroxyanisole to the total mass of the silver-based antibacterial composite is different, and the rest is substantially the same as Example 1 and will not be repeated here.
[0080] The performance of the antibacterial fibers with high color stability prepared in Examples 8-9 and Comparative Examples 6-7 was tested, and the results are shown in Table 4:
[0081] Table 4 Related properties of antibacterial fibers prepared in Examples 8-9 and Comparative Examples 6-7
[0082]
[0083] As shown in Table 4, when the content of silver ions, anti-ultraviolet agent and solid paraffin remains unchanged, as the content of antioxidant increases (Examples 1, 8, and 9), the initial antibacterial rate shows an upward trend, indicating that there is a certain synergistic effect between silver ions and antioxidants; at the same time, the oxidation resistance of the antibacterial fiber gradually increases. In addition, the light antibacterial rate also increases with the continuous increase of the antioxidant content, and the ultraviolet resistance of the antibacterial fiber is also enhanced, indicating that there is a certain synergistic effect between silver ions, antioxidants and anti-ultraviolet agents.
[0084] When the antioxidant content reaches a certain value, and then further increases the antioxidant content (Comparative Example 7), the antibacterial rate of the fiber after oxidation and the initial antibacterial rate are basically unchanged, that is, the antioxidant performance is basically at a constant value, and the cost will increase at the same time.
[0085] When the antioxidant content is low (Comparative Example 6), the antioxidant performance is weak, the oxidation antibacterial rate of the obtained antibacterial fiber decreases significantly, and the fiber is prone to discoloration in a short time.
[0086] Examples 10-11 and Comparative Examples 8-9
[0087] A method for preparing an antibacterial fiber with high color stability, compared with Example 1, is different in that in step S1, the proportion of benzophenone in the total mass of the silver-based antibacterial composite is different, and the rest is substantially the same as Example 1 and will not be repeated here.
[0088] The performance of the antibacterial fibers with high color stability prepared in Examples 10-11 and Comparative Examples 8-9 was tested, and the results are shown in Table 5:
[0089] Table 5 Related properties of antibacterial fibers prepared in Examples 10-11 and Comparative Examples 8-9
[0090]
[0091] It can be seen from Table 5 that, when the content of silver ions, antioxidants and solid paraffin remains unchanged, as the content of anti-ultraviolet agent continues to increase (Examples 1, 10, and 11), the light antibacterial rate increases with the continuous increase of the content of anti-ultraviolet agent, and the ultraviolet resistance of the antibacterial fiber is also enhanced; at the same time, although the initial antibacterial rate and the oxidative antibacterial rate have changed, the initial antibacterial rate and the oxidative antibacterial rate are generally high, which further illustrates that there is a certain synergistic effect between silver ions, antioxidants and anti-ultraviolet agents.
[0092] When the content of the anti-ultraviolet agent reaches a certain value and then further increases the content (Comparative Example 9), the antibacterial rate of the fiber after illumination, the initial antibacterial rate and the oxidative antibacterial rate remain basically unchanged, that is, the anti-ultraviolet performance is basically at a constant value, and the cost will also increase.
[0093] When the content of the anti-ultraviolet agent is low (Comparative Example 8), the anti-ultraviolet performance is weak, the light fastness is only level 2, and various antibacterial rates are also reduced.
[0094] Examples 12-13 and Comparative Examples 10-11
[0095] A method for preparing an antibacterial fiber with high color stability is provided. Compared with Example 1, the difference is that in step S2, the mass ratio of the silver antibacterial compound to PET is different, and the other parts are substantially the same as Example 1 and will not be repeated here.
[0096] The performance of the antibacterial fibers with high color stability prepared in Examples 12-13 and Comparative Examples 10-11 was tested, and the results are shown in Table 6:
[0097] Table 6 Related properties of antibacterial fibers prepared in Examples 12-13 and Comparative Examples 10-11
[0098]
[0099] It can be seen from Table 6 that within a certain range, as the content of the silver-based antibacterial compound increases (Examples 1, 12, and 13), the antibacterial property of the fiber continues to increase, and the tensile strength first increases and then decreases. The fibers at each ratio maintain good antibacterial, anti-ultraviolet and anti-oxidation properties. This is mainly because as the content of the silver-based antibacterial compound increases, the content of solid paraffin increases. The increase in solid paraffin can improve the interface interaction between kaolin and polyester, improve the uniformity of kaolin dispersion in the middle of polyester, and improve spinnability; at the same time, paraffin can absorb part of the heat, thereby having a certain protective effect on the anti-ultraviolet and antioxidant loaded in the kaolin, reducing thermal decomposition, and obtaining a high-performance antibacterial fiber with a special structure. In addition, low-content kaolin has a weaker reinforcing effect on fiber strength. When the kaolin content is high, it affects the continuity of the fiber to a certain extent, thereby affecting its tensile strength.
[0100] When the content of the silver-based antibacterial complex is too high (Comparative Example 10), firstly, the solid particle amount is too high and the spinneret is easily blocked. Secondly, the solid paraffin content is also too high, and the viscosity of the melt decreases during the melt spinning process, resulting in frequent fiber breakage during the spinning process, thereby affecting normal spinning.
[0101] When the content of the silver-based antibacterial compound is too low (Comparative Example 2), the antibacterial property of the fiber is poor.
[0102] Examples 14-15 and Comparative Example 12
[0103] A method for preparing an antibacterial fiber with high color stability is provided. Compared with Example 1, the difference lies in that in step S2, the temperature of melt spinning is different. The other aspects are substantially the same as Example 1 and will not be described in detail herein.
[0104] The performance of the antibacterial fibers with high color stability prepared in Examples 14-15 and Comparative Example 12 was tested. The results are shown in Table 7:
[0105] Table 7 Related properties of antibacterial fibers prepared in Examples 14-15 and Comparative Example 12
[0106]
[0107] It can be seen from Table 7 that within a certain range, as the spinning temperature continues to increase (Examples 1, 14, and 15), the initial antibacterial rate, oxidation antibacterial rate, and light antibacterial rate of the fiber decrease, but the overall effect is good.
[0108] When the spinning temperature is too high (Comparative Example 12), silver is easily oxidized and discolored during the spinning process, resulting in poor color fastness of the fiber; at the same time, the antibacterial property is also reduced; furthermore, the anti-ultraviolet and antioxidant agents are thermally decomposed at high temperatures, and the durability of the antibacterial agent is reduced accordingly.
[0109] The spinning temperature is set according to the melting point of the fiber-forming polymer and is generally set at about 20°C higher than the spinning masterbatch.
[0110] Comparative Example 13
[0111] A method for preparing an antibacterial fiber with high color stability is provided. Compared with Example 1, the difference is that in step S1, the surface of the composite kaolin is not coated with solid paraffin wax. The other steps are substantially the same as Example 1 and will not be described in detail herein.
[0112] The tensile strength of the antibacterial fiber obtained in Comparative Example 13 is only 60 MPa, which is significantly lower than the tensile strength of the fiber prepared in Example 1, further indicating that solid paraffin can improve the tensile strength of the fiber while improving the antibacterial effect and the durability effect. In addition, the presence of solid paraffin can increase the amount of silver antibacterial compound added during the spinning process, thereby changing the properties of the fiber.
[0113] Comparative Example 14
[0114] A method for preparing an antibacterial fiber with high color stability, compared with Example 1, the difference is that in step S1, paraffin is replaced with gel, and the dispersed gel liquid is prepared by the method of Chinese Example 3 with application number CN201810995339.8, and then the composite kaolin is placed in the dispersed gel liquid to adsorb the gel, and the rest is roughly the same as Example 1, which will not be repeated here. The gel contains water, so the setting of the gel cannot achieve melt spinning.
[0115] Comparative Example 15
[0116] A method for preparing an antibacterial fiber with high color stability is provided. Compared with Example 1, the difference lies in that in step S1, the antioxidant is replaced with ammonium dihydrogen phosphate and ammonium chloride, and the rest is substantially the same as Example 1 and will not be described herein.
[0117] Comparative Example 16
[0118] A method for preparing an antibacterial fiber with high color stability is provided. Compared with Example 1, the difference lies in that in step S1, only silver ions are adsorbed in kaolin, and the rest is substantially the same as Example 1 and will not be described in detail here.
[0119] Depend on Figure 1 It can be seen that after the antibacterial fibers prepared in Example 1 and Comparative Example 16 were stored under the same storage conditions for 3 months, the initial whiteness of the fibers prepared in Example 1 and Comparative Example 16 was the same. As shown in Figure a (left), the color of the fiber in Example 1 did not change substantially; as shown in Figure b (right), the color of the antibacterial fiber prepared in Comparative Example 16 became obviously black, further indicating that the antibacterial fiber obtained in the present invention has better performance.
[0120] The performance of the antibacterial fiber with high color stability prepared in Comparative Examples 15-16 was tested, and the results are shown in Table 8:
[0121] Table 8 Related properties of antibacterial fibers prepared in Comparative Examples 15-16
[0122]
[0123] It can be seen from Table 8 that when replaced with other oxidants (Comparative Example 15), the initial antibacterial rate, oxidation antibacterial rate and light antibacterial rate are all poor, and the oxidation whiteness grade and light whiteness grade are also significantly reduced, further illustrating that there is a certain synergistic effect between the silver ions, antioxidants and anti-ultraviolet agents of the present invention.
[0124] When kaolin does not contain an anti-ultraviolet agent and an antioxidant (Comparative Example 16), various properties are deteriorated.
[0125] In summary, the present invention provides an antibacterial fiber with high color stability and a preparation method thereof. First, kaolin with a reasonable particle size is selected to allow silver ions, antioxidants and anti-ultraviolet agents to be adsorbed on the surface and internal pores of the kaolin with a high specific surface area; then, low-temperature drying is performed to remove moisture without destroying the molecular structure of the antioxidant and the anti-ultraviolet agent; then, solid paraffin is evenly wrapped on the surface of the composite kaolin to maximize the stability of the composite structure adsorbed by kaolin during the melt spinning process, thereby preparing a high-performance antibacterial fiber with high color stability; the obtained antibacterial fiber with high color stability can prevent the silver-based antibacterial agent from changing color under light and oxidation conditions, solve the problem of color stability of the silver-based antibacterial fiber, and has a wide range of application scenarios.
[0126] The above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solution of the present invention.
Claims
1. A method for preparing an antibacterial fiber with high color stability, characterized in that: The steps include: S1. Using calcined kaolin with a particle size of 100-500 nm as a carrier to adsorb silver ions, antioxidants and anti-ultraviolet agents to obtain composite kaolin; then preheating the composite kaolin to 50-60° C. after low-temperature drying, and then quickly mixing it with solid paraffin powder, so that the end surface of the solid paraffin in direct contact with the composite kaolin melts and adheres to the composite kaolin, thereby achieving the coating of the kaolin by the solid paraffin to obtain a silver-based antibacterial composite; the proportions of the silver ions, antioxidants, anti-ultraviolet agents and solid paraffin in the total mass of the silver-based antibacterial composite are 30-40%, 5-10%, 3-5% and 5-10%, respectively; S2. The silver antibacterial complex obtained in step S1 is uniformly mixed with a high molecular polymer in a mass ratio of 3-9%:91-97%, and melt-spinned at a temperature not exceeding 260° C. to obtain an antibacterial fiber with high color stability, wherein the high molecular polymer is one of polyethylene, polypropylene, polyethylene terephthalate or polybutylene terephthalate.
2. The method for preparing antibacterial fiber with high color stability according to claim 1, characterized in that: In step S1, the temperature range of the low-temperature drying is room temperature-50°C; the low-temperature drying adopts one of low-temperature vacuum drying and low-temperature air flow drying.
3. The method for preparing antibacterial fiber with high color stability according to claim 1, characterized in that: In step S1, kaolin is used as a carrier to adsorb silver ions, antioxidants and anti-ultraviolet agents. Specifically, kaolin is first placed in a saturated concentration of silver nitrate solution and soaked for 30-50 minutes to adsorb silver ions; then the kaolin adsorbed with silver ions is placed in a saturated concentration of antioxidant and anti-ultraviolet mixed solution and soaked for 30-50 minutes to adsorb antioxidants and anti-ultraviolet agents.
4. The method for preparing antibacterial fiber with high color stability according to claim 3, characterized in that: In step S1, the antioxidant is one of butylated hydroxyanisole, butylated hydroxytoluene, propyl gallate or tert-butylhydroquinone; and the anti-ultraviolet agent is one of benzophenone or benzotriazole compounds.
5. An antibacterial fiber with high color stability, characterized in that: The antibacterial fiber is prepared by the method for preparing an antibacterial fiber with high color stability according to any one of claims 1 to 4.
Citation Information
Patent Citations
Method for preparing antibacterial mould-proof zeolite-based humidity controlling material
CN109095945A
Method for preparing silver-carrying ion and copper ion kaolin anti-bacteria agent
CN101347124A
Stabilized fertilizer and preparation method thereof
CN109456121A